Perilaku Bullying dalam Drama 3 Nen a Gimi: Ima Kara Mina-san wa, Hitojichi desu, karya Komura Naoko dan Suzuki Yuma - Pratama, Oktaviani Nindi; Lusiana, Yusida; Kadafi, Muammar (Universitas Diponegoro, 2023)
This research aims to analyze the forms of bullying and the factors that cause bullying in 3 Nen A Gumi: Ima Kara Mina-san wa, Hitojichi Desu drama by Komuro Naoko and Suzuki Yuma. The method used in this research is descriptive qualitative method. Screenshot of scenes and dialogues are used as data sources. This research is a sociological study of literature. The data retrieval method uses reading and note-taking technique. Data analysis techniques are presented descriptively. The theory used for the analysis is theory of bullying by Coloroso. The conclusion of the analysis shows that in this drama there are four forms of bullying, including verbal bullying, physical bullying, relational bullying, and cyberbullying. The most common form of bullying is verbal bullying. Morever, there are two factors that cause bullying, that is peer factor and social environmental conditions. <a href=